2010
DOI: 10.3390/molecules15118229
|View full text |Cite
|
Sign up to set email alerts
|

Study on Suitability of KOD DNA Polymerase for Enzymatic Production of Artificial Nucleic Acids Using Base/Sugar Modified Nucleoside Triphosphates

Abstract: Recently, KOD and its related DNA polymerases have been used for preparing various modified nucleic acids, including not only base-modified nucleic acids, but also sugar-modified ones, such as bridged/locked nucleic acid (BNA/LNA) which would be promising candidates for nucleic acid drugs. However, thus far, reasons for the effectiveness of KOD DNA polymerase for such purposes have not been clearly elucidated. Therefore, using mutated KOD DNA polymerases, we studied here their catalytic properties upon enzymat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 45 publications
(46 reference statements)
4
23
0
Order By: Relevance
“…[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] Veedu et al first tested B/L nucleotide incorporation using Phusion High Fidelity DNA polymerase, 9°Nm DNA polymerase, and Pfu DNA polymerase, and observed that the first and second of these three polymerases to exhibit superior stability in human plasma and target binding affinity (t 1/2 = 53 h, EC 50 = 2.0 nM) compared with TTA1 (t 1/2 = 42 h, EC 50 = 5.8 nM). In contrast, replacement with 2'-OMe nucleotides at the same positions, which yielded TTA1.1, resulted in a more than 2-fold decrease in binding affinity, although stability was substantially improved (t 1/2 = 49 h, EC 50 = 13.7 nM).…”
Section: Enzymatic Syntheses Of Bnasmentioning
confidence: 99%
See 2 more Smart Citations
“…[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] Veedu et al first tested B/L nucleotide incorporation using Phusion High Fidelity DNA polymerase, 9°Nm DNA polymerase, and Pfu DNA polymerase, and observed that the first and second of these three polymerases to exhibit superior stability in human plasma and target binding affinity (t 1/2 = 53 h, EC 50 = 2.0 nM) compared with TTA1 (t 1/2 = 42 h, EC 50 = 5.8 nM). In contrast, replacement with 2'-OMe nucleotides at the same positions, which yielded TTA1.1, resulted in a more than 2-fold decrease in binding affinity, although stability was substantially improved (t 1/2 = 49 h, EC 50 = 13.7 nM).…”
Section: Enzymatic Syntheses Of Bnasmentioning
confidence: 99%
“…84,85 This approach has been successfully implemented and was published in Science in 2012, and a variant of Tgo DNA polymerase derived from Thermococcus gorgonarius, PolC7, was created. 26 Another way is to design polymerase variants and assess their catalytic abilities one by one; 56 we discovered several KOD variants suitable for BNA syntheses in our collaboration with Toyobo Co., Ltd. These polymerases are promising candidates for applications in BNA aptamer selection and will be used as parent enzymes for further improvements.…”
Section: Enzymatic Syntheses Of Bnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore in investigating the properties of LNA nucleotides in aptamers, we and others, have focused on selecting aptamers using SELEX methods, front-loaded with LNA and other modified nucleotides. [19][20][21][22][23] Commercially available polymerases are capable of reading and incorporating LNA nucleotides, 22,24,25 but the efficacy of such reactions is often low. Despite this, Kasahara et al 19 recently reported the selection of aptamers containing LNA nucleotides in the primer and the random region.…”
Section: Introductionmentioning
confidence: 99%
“…To improve chemical diversity, base-modified DNA aptamers have been readily utilized, largely owing to the discovery that family B DNA polymerases (including Vent, KOD, and Pfu) can accommodate C5-substituted thymidine base analogs. 3, 1115, 1822 In particular, SOMAmer technology, which incorporates short hydrophobic groups at the C5 position of uridine, improved the success rate of obtaining high-affinity aptamers from 30% to 80% for hundreds of targets. 20 Recently, our group reported a method termed SELection of Modified Aptamers, or SELMA, allowing for the incorporation of large modifications into DNA libraries, which was successfully used to obtain multivalent glycoclusters that mimic a conserved epitope on the HIV envelope protein gp120.…”
mentioning
confidence: 99%